The impact of metakaolin on the hydration of tricalcium silicate: effect of C-A-S-H precipitation - Sowoidnich, T.; Cölfen, H.; Rößler, C.; Damidot, D.; Ludwig, H.-M. (Frontiers in Materials, 2023)
Metakaolin (MK) is used as supplementary cementitious material to reduce the CO2 footprint of Portland cements. However, the early hydration of Portland cement (OPC) is often retarded due to its use. The present work investigates the mechanisms of this retardation. Focus is laid on the interaction of MK with the main clinker phase C3S (Ca3SiO5, pure form of alite) that is known to govern the kinetics of early hydration of OPC. Hydration reactions of MK and C3S were analysed by optical emission spectroscopy, electron microscopy, thermal analysis, X-ray diffraction and reaction calorimetry. Results on MK showed that compared to sodium ions the presence of calcium ions reduced the maximum amounts of silicate and aluminate ions released into solution by MK. For MK + C3S mixtures, C-A-S-H was formed at the surfaces of both C3S and MK within minutes with a composition of (CaO)1.3(SiO2)0.8(Al2O3)0.2(H2O)2.7. The solubility constant of (CaO)1.3(SiO2)0.8(Al2O3)0.2(H2O)2.7 was determined. Moreover, C-A-S-H appeared to be an unsuitable substrate for C-S-H nucleation. Therefore, its formation during early hydration is expected to play an important role in the retardation of C3S hydration. Indeed, when C-A-S-H seeds are formed, less C-S-H seeds are formed leading to lengthen the duration of the induction period. The presence of sulfate ions reduces the amount of C-A-S-H seeds as most aluminate ions are consumed to form ettringite. Consequently, sulfate ions induce an increase of the hydration kinetics such as observed in MK + C3S mixtures.